A fundamentação das decisões impugnáveis por recursos excepcionais - Fernandes, José Marcelo Leal de Oliveira (2023)
The purpose of this work is to examine what are the conditions for the decisions appealable by extraordinary and special appeals to be considered really motivated. The fundamental elements of this work are identifying the singularities related to the exercise of the contradictory through extraordinary and special appeals and indicating the functions that must be fulfilled by judicial decision motivation. In order to achieve the goal of this research, it is examined the contradictory principle and its modern conception as well as its relation with the motivation of judicial decisions. It is also discussed the exercise of contradictory through the use of extraordinary and special appeals and its particularities. Essential aspects of judicial decision motivation are identified, particularly its functions and conditions. Lastly, these three matters are connected, with identification of parameters for judicial decisions appealable by extraordinary and special appeals to be considered truly motivated as well as identification of consequences and alternatives to the parties in case of motivation that does not fulfill these guidelines